The Effect of Knowledge on Mothers' Attitudes Towards the Benefits of Prenatal Massage (ENDORPHIN) on Back Pain in Mothers in Their Third Trimester of Pregnancy - Rini, Nisvia (Cattleya Darmaya Fortuna, 2024)
Discomfort is common in pregnant women during the third trimester, one of which is back pain. Around 80% of women experience back pain at various points during pregnancy. This occurs in 70% of cases due to changes in the muscles and bones of the back, while 30% may be caused by previous spinal conditions. Massage aims to restore venous and lymphatic circulation, stimulate sensory receptors in the skin and subcutaneous tissue to reduce pain. A preliminary study conducted at the midwifery clinic of Nur Kholidah Pulungan, S.Keb in November 2024 surveyed 25 pregnant women, of whom 9 (36%) complained of back pain during the third trimester. The aim of this study was to determine the effect of pregnancy massage on back pain in pregnant women and the difference in pain between the treatment and control groups. This study used a quasi-experimental method with a non-randomized pretest and posttest with a control group design. The study was conducted over 3 months, from September to November 2024. The sampling method was non-random sampling with purposive sampling technique. Data analysis was performed using the Wilcoxon and Mann-Whitney tests. The results showed a significant effect of pregnancy massage on back pain in third-trimester pregnant women with a probability value (p) of 0.000 < 0.05, and there was a difference in back pain between the treatment and control groups, proven by a value (p) of 0.000 < 0.05.